An anti-corrosion photovoltaic module and a method of manufacturing the same
By using low melt index and high melt index EVA resin material layers co-extruded into a double-layer encapsulation film in photovoltaic modules, and coating the busbars and solder strips with anti-corrosion coatings, the corrosion problem of EVA photovoltaic encapsulation film in high temperature and high humidity environments is solved, the light transmittance and output power of the modules are improved, and the production process is simplified.
Patent Information
- Application Number
- CN202311115249.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-08-31
AI Technical Summary
Existing EVA photovoltaic encapsulation films are prone to decomposition in high temperature and high humidity environments, producing acetic acid and hydroperoxides, which lead to corrosion of solder ribbons and busbars, affecting the output power and durability of photovoltaic modules. At the same time, the existing anti-corrosion layer has low utilization rate and complex production process.
A double- or multi-layer encapsulating film is formed by co-extruding low melt index EVA resin material layers and high melt index EVA resin material layers, and an anti-corrosion coating is applied to the busbars and solder strips of the photovoltaic cells to form an anti-corrosion photovoltaic module and avoid filler diffusion.
It improves the utilization rate of anti-corrosion coatings, simplifies production processes, maintains stable light transmittance and output power of photovoltaic modules, and extends service life.
Smart Images

Figure BDA0004424912900000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic module technology, and in particular to a corrosion-resistant photovoltaic module and its preparation method. Background Technology
[0002] When photovoltaic modules are used outdoors, the high temperature, high humidity, and strong sunlight conditions can cause the residual peroxide crosslinking agents in the photovoltaic encapsulation film system to decompose. The decomposed substances further form hydrogen peroxide, which is highly reactive and easily corrodes the solder ribbons on the surface of crystalline silicon photovoltaic cells, turning them into black silver oxide. Similarly, for ethylene vinyl acetate (EVA) photovoltaic encapsulation films, high temperature and high humidity environments can also cause EVA to decompose, producing acetic acid. Acetic acid corrodes the solder ribbons and busbars, reducing the output power of the photovoltaic module and decreasing its durability.
[0003] Therefore, in order to prevent corrosion of the solder ribbons and busbars inside photovoltaic modules, while maintaining stable output power and extending the service life of photovoltaic modules, it is urgent to solve the problem of metal corrosion of the solder ribbons and busbars inside photovoltaic modules caused by the decomposition products of acetic acid and / or hydroperoxide generated by photovoltaic encapsulation films (especially EVA photovoltaic encapsulation films) when used in high temperature and high humidity outdoor environments.
[0004] Therefore, CN112724851A discloses an encapsulation film comprising a substrate film layer and an anti-corrosion layer. After the substrate film layer and the anti-corrosion layer are cast into films, the anti-corrosion layer is cut to the appropriate size and adhered to the projection positions of the solder ribbons and busbars on the substrate film layer using adhesive. During photovoltaic module encapsulation, the anti-corrosion layer is placed on the side adjacent to the solar cell. While this solution solves the problem of reduced light transmittance of the EVA film caused by the addition of anti-corrosion filler, cutting the anti-corrosion layer to a specified size results in waste of the anti-corrosion layer, significantly reducing its utilization rate. Furthermore, using adhesive to bond the substrate film layer and the anti-corrosion layer increases production steps, raises the difficulty of the manufacturing process, and is not easily implemented, reducing the production efficiency of photovoltaic modules. Moreover, the anti-corrosion layer is bonded using adhesive.
[0005] Furthermore, the melt index of the EVA resin used in existing EVA encapsulation films is typically 1–400 g / 10 min (as shown in CN116496703A). Therefore, under normal circumstances, the EVA resin used in existing EVA encapsulation films contains not only low melt index EVA resin but also high melt index EVA resin. Consequently, existing EVA encapsulation films also have the problem of difficulty in effectively preventing the diffusion of fillers in anti-corrosion coatings inside photovoltaic modules. Therefore, after a period of use in outdoor high temperature and high humidity environments, the light transmittance of photovoltaic modules will still be affected. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a corrosion-resistant photovoltaic module and its preparation method.
[0007] Based on this, the present invention discloses a method for preparing a corrosion-resistant photovoltaic module, comprising the following preparation steps:
[0008] S1. Co-extrude a low melt index EVA resin material layer and a high melt index EVA resin material layer into a double-layer or multi-layer encapsulation film to obtain the EVA photovoltaic encapsulation film.
[0009] Among them, the melt index of EVA resin in the low melt index EVA resin material layer is less than or equal to 10 g / 10 min; the melt index of EVA resin in the high melt index EVA resin material layer is greater than or equal to 20 g / 10 min.
[0010] The thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer is 1:0.1 to 1:10.
[0011] S2. Apply anti-corrosion coating to the surface of the busbars and solder strips of the photovoltaic cell to obtain an anti-corrosion photovoltaic cell;
[0012] S3. Stack the photovoltaic front panel, the first EVA film, the corrosion-resistant photovoltaic cells, the second EVA film, and the photovoltaic back panel in sequence, and heat and laminate them to obtain the corrosion-resistant photovoltaic module.
[0013] Wherein, the first EVA film and the second EVA film are both EVA photovoltaic encapsulation films of step S1, and the low melt index EVA resin material layer in the EVA photovoltaic encapsulation film contacts the photovoltaic cell.
[0014] Preferably, in step S1, the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is 1:0.2 to 1:5.
[0015] More preferably, in the EVA photovoltaic encapsulation film, the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer is 1:0.5 to 1:2.
[0016] Preferably, in step S1, the total thickness of the EVA photovoltaic encapsulation film is 100–500 μm.
[0017] Preferably, in step S1, the VA content of the EVA resin used in the EVA photovoltaic encapsulation film is 20-35%.
[0018] Preferably, in step S1, both the low melt index EVA resin material layer and the high melt index EVA resin material layer are made by mixing EVA resin, initiator, crosslinking agent, silane coupling agent and ultraviolet light stabilizer in a mass ratio of 1000:5~8:3~6:2~5:0.8~1.2.
[0019] Preferably, in step S2, the raw materials of the anti-corrosion coating include fillers and vinyl acetate-ethylene copolymer emulsion, and the mass ratio of vinyl acetate-ethylene copolymer emulsion to filler in the anti-corrosion coating is 1:50-60. To enhance the coatability of the anti-corrosion coating, VAE emulsion is added.
[0020] More preferably, the filler is at least one of hydrotalcite, talc powder, magnesium hydroxide, magnesium oxide, calcium oxide, calcium hydroxide, zinc oxide, zinc hydroxide, barium oxide, barium hydroxide, aluminum oxide, aluminum hydroxide, magnesium carbonate, calcium carbonate, zinc carbonate, barium carbonate, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, or magnesium bicarbonate.
[0021] More preferably, the filler is a modified filler treated with at least one of silane coupling agents, titanate coupling agents, or rare earth coupling agents. The modified filler treated with coupling agents can enhance the bonding between the filler and the EVA resin material, thus helping to prevent the diffusion and migration of the filler to a certain extent.
[0022] More preferably, the particle size of the filler is 0.01 to 150 μm.
[0023] The present invention also discloses a corrosion-resistant photovoltaic module, which is prepared by the method described above in the present invention.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] In the method for preparing the corrosion-resistant photovoltaic module of the present invention, the corrosion-resistant coating is directly applied to the surface of the busbars and solder strips of the photovoltaic cell. This not only provides excellent corrosion resistance to the solder strips and busbars, avoiding corrosion of the solder strips and busbars by the decomposition products of the photovoltaic encapsulation film system under high temperature and high humidity conditions, but also improves the problem of reduced light transmittance caused by the addition of corrosion-resistant fillers in existing photovoltaic encapsulation films. Furthermore, it eliminates the need for cutting the corrosion-resistant layer, simplifies the preparation process, improves preparation efficiency, and effectively avoids waste of corrosion-resistant materials, thus resulting in higher utilization of the corrosion-resistant coating.
[0026] Furthermore, both the first and second EVA films utilize the EVA photovoltaic encapsulation film from step S1. This EVA photovoltaic encapsulation film is a double- or multi-layer encapsulation film formed by co-extruding a low melt index EVA resin material layer (melt index not greater than 10 g / 10 min) and a high melt index EVA resin material layer (melt index not less than 20 g / 10 min) at a thickness ratio of 1:0.1 to 1:10. The low melt index EVA resin material layer contacts the solar cell, while the high melt index EVA resin material layer is away from the solar cell. In this way, the low melt index EVA resin material layer can effectively avoid the problem of filler diffusion in the anti-corrosion coating inside the photovoltaic module. Therefore, the anti-corrosion photovoltaic module obtained by this invention not only has high initial transmittance, but also maintains high transmittance after long-term use in high temperature and high humidity environments, thereby enabling the module to maintain stable photovoltaic conversion efficiency. Detailed Implementation
[0027] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to specific embodiments.
[0028] Example 1
[0029] This embodiment of a method for preparing a corrosion-resistant photovoltaic module includes the following preparation steps:
[0030] Preparation of S1 and EVA photovoltaic encapsulating film:
[0031] EVA photovoltaic encapsulation film is a two- or multi-layer encapsulation film made by compounding a low melt index EVA resin material layer and a high melt index EVA resin material layer. This EVA photovoltaic encapsulation film can be obtained by co-extruding the low melt index EVA resin material layer and the high melt index EVA resin material layer into a two- or multi-layer encapsulation film.
[0032] The VA content of the EVA resin used in EVA photovoltaic encapsulation film is 20-35%.
[0033] Both the low melt index EVA resin material layer and the high melt index EVA resin material layer are composed of EVA resin, initiator, co-crosslinking agent, silane coupling agent, and UV stabilizer mixed in a mass ratio of 1000:5-8:3-6:2-5:0.8-1.2. In practice, the initiator, co-crosslinking agent, silane coupling agent, and UV stabilizer are all conventional additives used in existing EVA encapsulation films, and therefore will not be elaborated upon.
[0034] The EVA resin in the low melt index EVA resin material layer has a melt index of less than or equal to 10 g / 10 min, while the EVA resin in the high melt index EVA resin material layer has a melt index of greater than or equal to 20 g / 10 min.
[0035] The total thickness of the EVA photovoltaic encapsulation film is 100–500 μm. The thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is 1:0.1–1:10, preferably 1:0.2–1:5, and more preferably 1:0.5–1:2.
[0036] S2. Apply the anti-corrosion coating directly and evenly to the surface of the busbars and solder strips of the photovoltaic cell to obtain an anti-corrosion photovoltaic cell.
[0037] The coating methods include, but are not limited to, brushing, high-pressure airless spraying, electrostatic spraying, dip coating, or electrophoretic coating.
[0038] The raw materials of the anti-corrosion coating include fillers and vinyl acetate-ethylene copolymer (VAE) emulsion, and the mass ratio of VAE emulsion to filler in the anti-corrosion coating is 1:50 to 60 (e.g., 1:55).
[0039] The filler is at least one of the following: hydrotalcite, talc powder, magnesium hydroxide, magnesium oxide, calcium oxide, calcium hydroxide, zinc oxide, zinc hydroxide, barium oxide, barium hydroxide, aluminum oxide, aluminum hydroxide, magnesium carbonate, calcium carbonate, zinc carbonate, barium carbonate, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, or magnesium bicarbonate.
[0040] The filler is a modified filler that has been treated with at least one of silane coupling agent, titanate coupling agent or rare earth coupling agent.
[0041] The filler has a particle size of 0.01150 μm, preferably 50-100 μm.
[0042] S3. The photovoltaic front panel, the first EVA film, the photovoltaic cell, the second EVA film and the photovoltaic back panel are stacked in sequence in a vacuum laminator and heated and laminated to obtain the corrosion-resistant photovoltaic module.
[0043] In this process, both the first EVA film and the second EVA film are EVA photovoltaic encapsulation films prepared in step S1. The low melt index EVA resin material layer in the EVA photovoltaic encapsulation film is in contact with the solar cell, while the high melt index EVA resin material layer is far away from the solar cell.
[0044] Among them, the photovoltaic cell is the corrosion-resistant photovoltaic cell of step S2.
[0045] The photovoltaic front panel is made of photovoltaic glass or other existing non-glass photovoltaic front panels. The photovoltaic back panel is made of photovoltaic glass or other existing non-glass photovoltaic back panels.
[0046] The heating and laminating conditions in the vacuum laminator are: laminating at 135-150℃ for 500-600 seconds.
[0047] Example 2
[0048] The method for preparing a corrosion-resistant photovoltaic module in this embodiment follows the same preparation steps as in Example 1, but differs from Example 1 in that:
[0049] In step S1, the EVA photovoltaic encapsulating film is a double-layer encapsulating film formed by co-extrusion casting of a low melt index EVA resin material layer and a high melt index EVA resin material layer. That is, the EVA photovoltaic encapsulating film has one low melt index EVA resin material layer and one high melt index EVA resin material layer.
[0050] Both the low melt index EVA resin material layer and the high melt index EVA resin material layer are composed of EVA resin, initiator, co-crosslinking agent, silane coupling agent, and UV stabilizer mixed in a mass ratio of 1000:6:5:3:1. The melt index of the EVA resin in the low melt index EVA resin material layer is 8 g / 10 min, while the melt index of the EVA resin in the high melt index EVA resin material layer is 25 g / 10 min.
[0051] The total thickness of the EVA photovoltaic encapsulation film is 450 μm; and the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is 1:0.5.
[0052] In step S2, the filler used in the anti-corrosion coating is magnesium oxide treated with silane coupling agent, and the particle size of the filler is 50 μm.
[0053] In step S3, the photovoltaic front panel is photovoltaic glass; while the photovoltaic back panel is an existing non-glass photovoltaic back panel.
[0054] Example 3
[0055] The method for preparing a corrosion-resistant photovoltaic module in this embodiment follows the same preparation steps as in Embodiment 2, but differs from Embodiment 2 in that:
[0056] In step S1, the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is 1:2.
[0057] Comparative Example 1
[0058] The preparation method of the corrosion-resistant photovoltaic module in this comparative example is the same as that in Example 2, except that:
[0059] Step S2 is omitted, meaning that the busbars and solder strips of the photovoltaic cell in this comparative example are not coated with anti-corrosion coating. Therefore, the photovoltaic cell in step S3 is a non-corrosion-resistant photovoltaic cell.
[0060] Comparative Example 2
[0061] The method for preparing a corrosion-resistant photovoltaic module in this embodiment follows the same preparation steps as in Embodiment 2, but differs from Embodiment 2 in that:
[0062] In step S1, the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is 1:20.
[0063] Comparative Example 3
[0064] The method for preparing a corrosion-resistant photovoltaic module in this embodiment follows the same preparation steps as in Embodiment 2, but differs from Embodiment 2 in that:
[0065] In step S1, the EVA photovoltaic encapsulation film is a single-layer encapsulation film with only a high melt index EVA resin material layer (without a low melt index EVA resin material layer), and the thickness of the single-layer encapsulation film is 450 μm. Therefore, in step S3, the high melt index EVA resin material layer contacts the solar cell.
[0066] Performance testing
[0067] The corrosion-resistant photovoltaic modules prepared in Examples 2-3 and Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in Table 1 below:
[0068] 1. Evaluation of corrosion and filler diffusion in anti-corrosion photovoltaic modules: Encapsulation tests of anti-corrosion photovoltaic modules were conducted using EVA photovoltaic encapsulation films from Examples 2-3 and Comparative Examples 1-3, respectively. The photovoltaic glass, first EVA film, photovoltaic cell, second EVA film, and photovoltaic backsheet were placed in a vacuum laminator in that order and laminated at 145°C (vacuuming for 330s, lamination for 540s) to obtain anti-corrosion photovoltaic modules. The filler diffusion in the anti-corrosion coating of the anti-corrosion photovoltaic modules and the appearance corrosion of the solder ribbons and busbars of the anti-corrosion photovoltaic modules after 2000 hours of high-temperature and high-humidity aging (85°C, 85%RH) were observed by EL (Electroluminescent) tracking.
[0069] 2. Transmittance Test of EVA Photovoltaic Encapsulation Film (hereinafter referred to as "film"): Transmittance tests were conducted on the corrosion-resistant photovoltaic modules of Examples 2-3 and Comparative Examples 1-3 after lamination. Transmittance was measured according to GB / T 2410-2008, using a UV-Vis spectrophotometer to determine the transmittance of the EVA photovoltaic encapsulation film in the 700-400 nm range. In Table 1 below, the transmittance after aging refers to the transmittance of the corrosion-resistant photovoltaic module after 2000 hours of high-temperature and high-humidity aging (85℃, 85% RH).
[0070] Table 1
[0071]
[0072] As shown in Table 1:
[0073] In Comparative Example 1, the corrosion-resistant photovoltaic module did not have an anti-corrosion coating directly applied to the solder strips and busbars. Therefore, after 2000 hours of high-temperature and high-humidity aging (85°C, 85% RH), corrosion occurred in the solder strips and busbars. However, in Examples 2 and 3 of this invention, the corrosion-resistant photovoltaic modules showed virtually no corrosion in the solder strips and busbars after 2000 hours of high-temperature and high-humidity aging (85°C, 85% RH).
[0074] As can be seen from Example 2 and Comparative Example 3, compared with Comparative Example 3, in the anti-corrosion photovoltaic module of Example 2 of the present invention, the low melt index EVA resin material layer in the EVA photovoltaic encapsulation film is contacted with the solar cell (instead of the high melt index EVA resin material layer contacting the solar cell), which can effectively prevent the filler in the anti-corrosion coating from diffusing inside the anti-corrosion photovoltaic module and causing a decrease in the light transmittance of the anti-corrosion photovoltaic module (this is because: compared with the high melt index EVA resin material, the low melt index EVA resin material diffuses more slowly at the same temperature), greatly improving the initial light transmittance and the light transmittance after high temperature and high humidity aging of the anti-corrosion photovoltaic module of the present invention, thereby improving the output power of the anti-corrosion photovoltaic module.
[0075] As can be seen from Example 2 and Comparative Example 2, if the ratio of the thickness of the low melt index EVA resin material layer to the thickness of the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film of Comparative Example 2 is too high, it will lead to a decrease in the light transmittance of the anti-corrosion photovoltaic module, and the light transmittance of the photovoltaic module of Comparative Example 2 also decreases significantly after high temperature and high humidity aging.
[0076] Furthermore, the inventors discovered that if the EVA photovoltaic encapsulation film is a single-layer encapsulation film with a thickness of 450 μm and only has a low melt index EVA resin material layer (without a high melt index EVA resin material layer), or if the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is less than 1:0.1, then the EVA photovoltaic encapsulation film can also prevent the diffusion of fillers in the anti-corrosion coating. However, the low melt index EVA resin material is more difficult to process than the high melt index EVA resin material, which will increase the difficulty of preparing the EVA photovoltaic encapsulation film and affect its preparation efficiency, so it is not advisable.
[0077] Although preferred embodiments of the present invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present invention.
[0078] The technical solution provided by the present invention has been described in detail above. Specific examples have been used to illustrate the principle and implementation of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core idea of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation and application scope based on the idea of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A method for preparing a corrosion-resistant photovoltaic module, characterized in that, The preparation steps include the following: S1. A multilayer encapsulating film is prepared by co-extruded a low melt index EVA resin material layer and a high melt index EVA resin material layer into an EVA photovoltaic encapsulating film. Among them, the melt index of EVA resin in the low melt index EVA resin material layer is less than or equal to 10 g / 10 min; the melt index of EVA resin in the high melt index EVA resin material layer is greater than or equal to 20 g / 10 min. The thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer is 1:0.1 to 1:
10. In step S1, both the low melt index EVA resin material layer and the high melt index EVA resin material layer are made by mixing EVA resin, initiator, co-crosslinking agent, silane coupling agent and ultraviolet light stabilizer in a mass ratio of 1000:5~8:3~6:2~5:0.8~1.
2. S2. Apply anti-corrosion coating to the surface of the busbars and solder strips of the photovoltaic cell to obtain an anti-corrosion photovoltaic cell; S3. Stack the photovoltaic front panel, the first EVA film, the corrosion-resistant photovoltaic cells, the second EVA film, and the photovoltaic back panel in sequence, and heat and laminate them to obtain the corrosion-resistant photovoltaic module. Wherein, the first EVA film and the second EVA film are both EVA photovoltaic encapsulation films obtained in step S1, and the low melt index EVA resin material layer in the EVA photovoltaic encapsulation film contacts the photovoltaic cell.
2. The method for preparing a corrosion-resistant photovoltaic module according to claim 1, characterized in that, In step S1, the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer in the EVA photovoltaic encapsulation film is 1:0.2 to 1:
5.
3. The method for preparing a corrosion-resistant photovoltaic module according to claim 2, characterized in that, In the EVA photovoltaic encapsulation film, the thickness ratio of the low melt index EVA resin material layer to the high melt index EVA resin material layer is 1:0.5 to 1:
2.
4. The method for preparing a corrosion-resistant photovoltaic module according to claim 1, characterized in that, In step S1, the total thickness of the EVA photovoltaic encapsulation film is 100-500 μm.
5. The method for preparing a corrosion-resistant photovoltaic module according to claim 1, characterized in that, In step S1, the VA content of the EVA resin used in the EVA photovoltaic encapsulation film is 20-35%.
6. The method for preparing a corrosion-resistant photovoltaic module according to claim 1, characterized in that, In step S2, the raw materials of the anti-corrosion coating include fillers and vinyl acetate-ethylene copolymer emulsion, and the mass ratio of vinyl acetate-ethylene copolymer emulsion to filler in the anti-corrosion coating is 50~60:
1.
7. The method for preparing a corrosion-resistant photovoltaic module according to claim 6, characterized in that, The filler is at least one of the following: hydrotalcite, talc powder, magnesium hydroxide, magnesium oxide, calcium oxide, calcium hydroxide, zinc oxide, zinc hydroxide, barium oxide, barium hydroxide, aluminum oxide, aluminum hydroxide, magnesium carbonate, calcium carbonate, zinc carbonate, barium carbonate, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, or magnesium bicarbonate.
8. The method for preparing a corrosion-resistant photovoltaic module according to claim 6, characterized in that, The filler is a modified filler that has been treated with at least one of silane coupling agent, titanate coupling agent or rare earth coupling agent. The particle size of the filler is 0.01 to 150 μm.
9. A corrosion-resistant photovoltaic module, characterized in that, The corrosion-resistant photovoltaic module is prepared by the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Packaging adhesive film
CN112724851A
EVA photovoltaic packaging adhesive film and preparation method thereof
CN116496703A
White packaging adhesive film and preparation method thereof, and photovoltaic assembly comprising white packaging adhesive film
CN111171733A
High-infrared-reflection black barrier packaging adhesive film, preparation method thereof and photovoltaic module
CN116494620A
